Demographic and Socioeconomic Factors Influencing Public Attitudes Toward a Presumed Consent System for Organ Donation Without and With a Priority Allocation Scheme - Tumin, M.; Tafran, K.; Mutalib, M.A.T.A.; Satar, N.M.; Said, S.M.; Adnan, W.A.H.W.M.; Lu, Y.S. (Lippincott, Williams & Wilkins, 2015)
The influence of demographic and socioeconomic factors on the public's attitude towards a presumed consent system (PCS) of organ donation was estimated in 2 scenarios: without and with a priority allocation scheme (PAS). Self-Administered questionnaires were completed by 775 respondents. Using multiple logistic regressions, respondents' objections to donating organs in both scenarios were estimated. In total, 63.9% of respondents would object to donating under a PCS, whereas 54.6% would object under a PCS with a PAS. Respondents with pretertiary education were more likely to object than were respondents with tertiary education, in both the first (adjusted odds ratio [AOR]=1.615) and second (AOR=1.728) scenarios. Young respondents were less likely to object than were middle-Aged respondents, in both the first (AOR=0.648) and second (AOR=0.572) scenarios. Respondents with mid-ranged personal monthly income were more likely to object than were respondents with low income, in both the first (AOR=1.994) and second (AOR=1.519) scenarios. It does not seem that Malaysia is ready to implement a PCS. The educational level, age, and income of the broader public should be considered if a PCS, without or with a PAS, is planned for implementation in Malaysia.